2012
DOI: 10.1016/j.jcrs.2011.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis to manage refractive errors after deep anterior lamellar keratoplasty

Abstract: Treatment of post-DALK keratoconus patients with LASIK to correct manifest refraction error seems to be a viable option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…The magnitude of the baseline spherical error (range +3.0 to −13.0 D) and cylindrical error (range −2.0 to −11.0 D) of this case series reflect the wide field of power range provided by phakic IOLs. These baseline refractive values were much higher than those revealed in most of the reports of LASIK postkeratoplasty, including DALK 15,16. Moreover, the percentage of reduction in refractive astigmatism (83.8±15.8%) was higher when compared to LASIK after keratoplastly, which varies from 48% to 88% in different reports of the literature 19–24…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The magnitude of the baseline spherical error (range +3.0 to −13.0 D) and cylindrical error (range −2.0 to −11.0 D) of this case series reflect the wide field of power range provided by phakic IOLs. These baseline refractive values were much higher than those revealed in most of the reports of LASIK postkeratoplasty, including DALK 15,16. Moreover, the percentage of reduction in refractive astigmatism (83.8±15.8%) was higher when compared to LASIK after keratoplastly, which varies from 48% to 88% in different reports of the literature 19–24…”
Section: Discussionmentioning
confidence: 68%
“…Acar et al15 also described a significant improvement in UDVA with LASIK after DALK, without eyes losing CDVA lines. Recently, Sorkin et al14 reported a significant improvement in CDVA and UDVA in 34 eyes submitted to PRK postkeratoplasty.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Banu Toru Acar recently reported good refractive results after either 1-step or 2-step microkeratome LASIK procedures in a retrospective 13 eyes case series. 22 To our knowledge, this is the first paper on the application of Femto-LASIK for ametropia correction in post-DALK patients using the tissue-saving or customvue or standard visx treatment. This series has demonstrated that Femto-LASIK after a corneal lamellar graft can be a safe and effective procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Separate removal of the interrupted sutures allows for good management of postoperative astigmatism. Relaxing incisions [81] , laser-assisted in situ keratomileusis [82] , or Artisan iris-fixed toric phakic intraocular lenses [83] could be good options in selective cases.…”
Section: Late Complicationsmentioning
confidence: 99%